On-line Flexible Marshalling and Coupling Operations in Different Scenarios - FAN Yinghui (Chengshi guidao jiaotong yanjiu)
［Objective］To address the issues of uneven passenger flow distribution over time and space, there is a need to conduct research on flexible marshalling and coupling operations in different scenarios. ［Method］The contents and characteristics of coupling operations in pre-station and post-station turn-back scenarios are qualitatively analyzed. A flexible marshalling simulation system is used to simulate and calculate the time required for each stage in coupling operations, further providing references for the turn-back forms of lines that adopt flexible marshalling. ［Result & Conclusion］Compared to the pre-station operation scenarios, the time required for coupling operations is longer in post-station scenarios. For lines using flexible train marshalling technology, it is recommended to adopt pre-station turn-back operation at terminal stations with direct connection to parking lots or depots, thereby significantly improving the efficiency of coupling operations. At intermediate stations, the post-station turn-back is more suitable.